Isotope effect on water adsorption on hydrophobic carbons of different nanoporosities. (August 2017) - Ono, Yuji; Futamura, Ryusuke; Hattori, Yoshiyuki; Utsumi, Shigenori; Sakai, Toshio; Kaneko, Katsumi
Abstract: The adsorption isotherms of H2 O and D2 O on pitch-based activated carbon fibers (ACFs) of different pore widths from 0.6 to 1.5 nm were measured at 298 K. Briefly speaking, the D2 O adsorption isotherms are close to the H2 O adsorption isotherms. However, we observed an evident difference in the rising and desorption relative pressures for the H2 O and D2 O adsorption isotherms. The D2 O adsorption rises at a higher relative pressure than the H2 O adsorption. Correspondingly the D2 O desorption occurs at a higher relative pressure than the H2 O desorption. Detailed comparison of the H2 O and D2 O adsorption isotherms confirmed a reproducible difference over the whole relative pressure range. The different adsorption behavior of H2 O and D2 O in the hydrophobic micropores is discussed with the relevance to the difference in the hydrogen bonding of H2 O and D2 O. Graphical abstract: